Acute myeloid leukaemia (AML) with t(6;9)(p23;q34) is associated with poor outcome in childhood AML regardless of FLT3‐ITD status: a report from the Children's Oncology Group. (25th March 2014) - Tarlock, Katherine; Alonzo, Todd A.; Moraleda, Pilar P.; Gerbing, Robert B.; Raimondi, Susana C.; Hirsch, Betsy A.; Ravindranath, Yaddanapudi; Lange, Beverly; Woods, William G.; Gamis, Alan S.; Meshinchi, Soheil
Summary: Acute myeloid leukaemia (AML) with t(6;9)(p23;q34) is a rare subtype associated with FLT3 ‐internal tandem duplication (ITD) and poor outcomes. The clinical outcomes of paediatric patients with t(6;9) with and without FLT3 ‐ITD treated on six consecutive cooperative trails were evaluated. In contrast to patients without t(6;9), those with t(6;9) had a significantly lower complete remission rate, higher relapse rate (RR), and poor overall survival (OS). Within t(6;9) patients, those with and without FLT3 ‐ITD had an OS of 40% and 27% respectively ( P > 0·9), demonstrating that t(6;9) is a high‐risk cytogenetic feature in paediatric AML and its clinical impact is independent of the presence of FLT3 ‐ITD.